1964
DOI: 10.1017/s0022029900017866
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the concentration of vitamins in milk: I. Effect of breed, season and geographical location on fat-soluble vitamins

Abstract: TWO surveys were done, one in 1943-44 and one in 1958-60, of the seasonal variation in the concentration of vitamin A and carotene in milk fat from 13 different areas in Great Britain. In the 1958-60 survey a-tocopherol and vitamin D were also measured. The main purpose of the second survey was to find out if the marked swing from Shorthorns to Friesians, and the trend towards greater use of carotene-rich foods in winter feeds that occurred in the intervening 15 years, had affected the pattern of vitamin A act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

1969
1969
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 37 publications
3
9
0
Order By: Relevance
“…The milk fat colour curve (Fig. 1, Winkelman et al, 1999) adapted to predict the mid-point of each period as a percentage of the lactation day one value was similar to those recorded for New Zealand bulk milk (McDowell and McDo- well, 1953; Thompson et al, 1964;Keen, 1986;Keen and Wilson, 1993).…”
Section: Calculation Of Milk Fat Colour Over the Lactationsupporting
confidence: 64%
“…The milk fat colour curve (Fig. 1, Winkelman et al, 1999) adapted to predict the mid-point of each period as a percentage of the lactation day one value was similar to those recorded for New Zealand bulk milk (McDowell and McDo- well, 1953; Thompson et al, 1964;Keen, 1986;Keen and Wilson, 1993).…”
Section: Calculation Of Milk Fat Colour Over the Lactationsupporting
confidence: 64%
“…Evidence suggests that this seasonal variation is the result of insufficient stores of vitamin D in the liver and fat tissues for mobilisation in times when dietary intake of the vitamin is low (18) . Many subsequent studies have confirmed the seasonal variation of the vitamin D content of milk (approximate differences ranging between 0•004 and 0•0014 µg/g fat) across different countries and breeds of cattle (Table 1) (19)(20)(21)(22) . Although seasonal variation in vitamin D content is widely reported in the literature, units of measurement are inconsistent, which makes it difficult to compare between studies.…”
Section: Seasonal Changes In Vitamin D Contentmentioning
confidence: 86%
“…The xanthophyll and β-carotene contents in cheese fat were the richest with the Montbéliarde breed and the poorest with the Abondance breed, respectively. Several studies have previously observed an effect of the cow's breed on the carotenoid content in milk fat [29,41,65,71], but none have experimentally compared these three breeds to our knowledge. The variations in the carotenoid content in milk fat related to the cow's breed could be due to differences between breeds of: (1) intestinal conversion of β-carotene into retinal by the 15, 15' dioxygenase [29], (2) quantitative secretion of β-carotene from plasma into milk [37] and/or (3) β-carotene storage and mobilization [67].…”
Section: Genetic and Physiological Factorsmentioning
confidence: 99%